Effects of Saliva From Periodontally Healthy and Diseased Subjects on Barrier Function and the Inflammatory Response in in vitro Models of the Oral Epithelium - Roy, Antoine; Ben Lagha, Amel; Gonçalves, Reginaldo; Grenier, Daniel (Frontiers in oral health, 2022)
Background: Periodontitis is a multifactorial, bacteria-mediated chronic inflammatory disease that results in the progressive destruction of the tooth-supporting tissues. It is well-known that saliva from subjects suffering from this disease generally contains higher levels of pro-inflammatory mediators, matrix metalloproteinases (MMP), and bacteria-derived toxic products. The aim of this study was to investigate and compare the effects of saliva from periodontally healthy and diseased subjects on the barrier function and inflammatory response in in vitro models of the oral epithelium. Methods: Unstimulated saliva samples from two groups of subjects, one with a healthy periodontium ( n = 12) and one with severe generalized periodontitis ( n = 11), were filter-sterilized. All the saliva samples were analyzed using an immunological multiplex assay to determine the levels of various cytokines and MMPs relevant to periodontitis. The impact of saliva on epithelial barrier integrity was assessed by monitoring transepithelial electrical resistance (TER) in an oral epithelium model using the B11 keratinocyte cell line. GMSM-K oral epithelial cells were treated with saliva from both groups to determine their ability to induce the secretion of interleukin-6 (IL-6) and interleukin-8 (IL-8), as determined by an enzyme-linked immunosorbent assay (ELISA). Results: Saliva from the periodontitis subjects contained significantly higher concentrations of matrix metalloproteinase-8 (MMP-8), matrix metalloproteinase-9 (MMP-9), IL-8, and C-X-C motif chemokine ligand 1 (CXCL1) compared to saliva from the healthy subjects. Saliva from the healthy and periodontitis subjects affected cytokine secretion and TER in a similar manner. More specifically, saliva from both groups increased TER and induced IL-6 and IL-8 secretion in the in vitro oral epithelium models used. Conclusion: Independently of the presence or absence of periodontitis, saliva can increase the relative TER and the secretion of IL-6 and IL-8 in in vitro models of the oral epithelium.